Ser mulher, ser humano? um estudo com mulheres encarceradas na Unidade Prisional de Ressocialização de Davinópolis - MA - MORAES, Wennedy da Mata (2022)
Aiming to understand the relationship between incarcerated women and their families, the present study is based on the analysis of the socio-structural reality present in the female prison system, so that it is possible to reflect on themes such as stigma, exclusion and punitive state. of prison in the context of gender inequalities. Through interviews with women incarcerated at the Prison Unit for Resocialization of Davinópolis/MA, we seek to find an answer to the following problem: How does the relationship between incarcerated women and their families occur and what are the assessments that women make of this relationship? The sociological approaches around critical sociological criminology, especially the feminist one, become important for such research to be expanded, taking into account the studies of Davis (2019), Lemgruber (1985), Foucault (1999), among other authors who starts to correspond efforts around the dialogues on the social state of the prison. As a preliminary result, it is observed that, sometimes, the state in which incarcerated women find themselves creates visible and invisible barriers that permeate the family relationship with those who are outside. This tends to have an effect on the notion of social belonging and on the process of social reintegration of those incarcerated.